Barrio Yungay and its particular functions (Polis (Santiago), 2018)
The author provides an overview of the Yungay area, from the conceptual and historical point of view to the study of the perception about it of its present inhabitants. What stands out as one of the oldest ‘barrios’ in the city of Santiago, and today one of the twelve larger neighborhoods over the commune of Santiago. This paper also presents studies about its functions, such as transportation services, commercial equipment, administrative, social, cultural and leisure activity.
Keywords: neighborhood Yungay; urbanization; great Santiago; local history